Neurological Involvement in COVID-19 Among Non-Hospitalized Adolescents and Young Adults - Havdal, Lise Beier; Berven, Lise Lund; Selvakumar, Joel; Stiansen-Sonerud, Tonje; Leegaard, Truls Michael; Tjade, Trygve; Zetterberg, Henrik; Blennow, Kaj; Wyller, Vegard Bruun Bratholm (Frontiers in Neurology, 2022)
Introduction Coronavirus disease 2019 (COVID-19) is prevalent among young people, and neurological involvement has been reported. We investigated neurological symptoms, cognitive test results, and biomarkers of brain injury, as well as associations between these variables in non-hospitalized adolescents and young adults with COVID-19. Methods This study reports baseline findings from an ongoing observational cohort study of COVID-19 cases and non-COVID controls aged 12–25 years (Clinical Trials ID: NCT04686734). Symptoms were charted using a standardized questionnaire. Cognitive performance was evaluated by applying tests of working memory, verbal learning, delayed recall, and recognition. The brain injury biomarkers, neurofilament light chain (NfL) and glial fibrillary acidic protein (GFAp), were assayed in serum samples using ultrasensitive immunoassays. Results A total of 405 COVID-19 cases and 111 non-COVID cases were prospectively included. Serum Nfl and GFAp concentrations were significantly elevated in COVID-19 cases as compared with non-COVID controls (p = 0.050 and p = 0.014, respectively). The COVID-19 cases reported more fatigue (p < 0.001) and post-exertional malaise (PEM) (p = 0.001) compared to non-COVID-19 controls. Cognitive test performance and clinical neurological examination did not differ across the two groups. Within the COVID-19 group, there were no associations between symptoms, cognitive test results, and NfL or GFAp levels. However, fatigue and PEM were strongly associated with older age and female sex. Conclusions Non-hospitalized adolescents and young adults with COVID-19 reported more fatigue and PEM and had slightly elevated levels of brain injury markers, but showed normal cognitive performance. No associations were found between symptoms, brain injury markers, and cognitive test results, but fatigue and PEM were strongly related to female sex and older age.